Take control of untangling connections : solve problems with USB, Thunderbolt, HDMI, DisplayPort, ethernet, audio - Fleishman, Glenn (Take control., 2022)
Frustrated with your peripheral cables? Tangled up in standards and compatibility? Glenn Fleishman figuratively cuts through the mess of ports, cables, and protocols with his new book, Take Control of Untangling Connections. The book sets out to answer the most common questions and troubleshoot frequently occurring problems. You’ll learn how to buy the best cable, identify the cables you have, and recognize and research ports. You get all the answers on how to connect USB, Thunderbolt, Ethernet, DisplayPort, HDMI, and audio at the fastest, best, or highest-fidelity method available. We spend our lives plugging stuff into our computers, smartphones, tablets, and other hardware. Why is it so hard to make it all work as we expect? Glenn Fleishman knows the answer to this: standards don’t develop in lock step, and whenever anything is out of sync, we wind up with frustration. He also knows the questions! As a writer about all things Apple for decades, he has used multiple generations of interface and connection standards, and he reads hundreds of questions a months from readers wrestling with their gear. Take Control of Untangling Connections is his attempt to put power (and video and data and more) back in your hands by helping you cut through cable clutter and confusion and find the right plug for the right jack—and the right cable. The book covers data networking with USB, Thunderbolt, and Ethernet; audio and video over DisplayPort, HDMI, and USB-C; and all the ins and outs of recognizing ports, researching your requirements, and finding or buying the right cables, adapters, and converters. There’s even a chapter on physical decluttering: how to organize your cables in your home and office.